Composite solution for realizing temperature sensing function of cement-based material, temperature sensor and preparation method

By designing a composite solution containing carbon nanotubes, superplasticizers and high-solid content ethylene-vinyl acetate copolymer emulsion, a conductive network structure of carbon nanotubes with polymer film coated is formed, and the problem of unstable existing cement-based material temperature sensors in low temperature environments is solved, and a cement-based temperature sensor with good temperature recognition accuracy and stability in both normal temperature and severe cold and frozen environments is realized.

CN119504170APending Publication Date: 2025-02-25GUANGZHOU MARITIME INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411659085.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing cement-based material temperature sensors are unstable in low temperature environments and are difficult to meet the temperature monitoring needs in severe cold and frozen environments.

Method used

A composite solution was designed, including carbon nanotubes, superplasticizers and high-solid content ethylene-vinyl acetate copolymer emulsion, prepared by high-speed shear mixing to form a conductive network structure of carbon nanotubes with polymer film coated, and used to prepare cement-based temperature sensors.

Benefits of technology

It achieves good temperature recognition accuracy and stability in normal temperature and cold and frozen environments, avoids moisture entering the conductive channel and affects the perception accuracy, and significantly improves the linearity of the temperature sensor and the monitoring reliability in low-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504170A_ABST
    Figure CN119504170A_ABST
Patent Text Reader

Abstract

The invention discloses a composite solution for realizing a temperature sensing function of a cement-based material, a temperature sensor and a preparation method of the temperature sensor, and the composite solution comprises the following components in parts by mass: 0.2-0.4 part of carbon nanotubes; 1-3 parts of a super plasticizer; 8 to 14 parts of ethylene-vinyl acetate copolymer emulsion; and 18-22 parts of water. According to the invention, the ethylene-vinyl acetate copolymer emulsion and the super plasticizer are added while the carbon nanotubes are added into the cement-based temperature sensing composite solution, so that not only can the dispersion uniformity and stability of the carbon nanotubes be improved, but also a carbon nanotube conductive network coated with a polymer film surface can be formed in a cement hydration process. When used as a sensor under natural conditions, the sensor has a good temperature self-monitoring function. And especially under the negative temperature condition, the temperature identification accuracy and stability of the sensor can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a composite solution, a temperature sensor and a preparation method for realizing the temperature sensing function of cement-based materials. Background Art

[0002] As a widely used material in modern buildings, the performance of concrete is directly affected by temperature. Especially in cold climates, concrete is very prone to structural damage such as frost heave damage, which is more common in high-altitude areas. The damage caused by severe cold and freezing not only affects the normal use of buildings, but may also pose a threat to their structural safety. Therefore, it is particularly important to accurately monitor the temperature of concrete in low-temperature environments. Traditional temperature sensors, including thermometers and embedded sensors, have defects such as high prices, low lifespans, and complex installation processes, which make it difficult to meet modern engineering needs.

[0003] Patent document CN 103674300 A prepares a carbon nanotube / cement-based composite temperature sensor by mixing a carbon nanotube dispersion and cement. According to the monotonic change of the resistivity of the material with temperature, the resistivity of the carbon nanotube / cement-based composite is measured with a multimeter to obtain the ambient temperature, but its applicable temperature range is only above 0°C.

[0004] Therefore, it is necessary to develop a cement-based temperature sensor that has good compatibility with concrete structures and long service life, which not only has good self-monitoring function under normal temperature conditions, but also has excellent stability in severe cold and freezing environments. Summary of the invention

[0005] Based on the deficiencies of the prior art, the present invention provides a composite solution for realizing the temperature sensing function of cement-based materials by designing a formula. The solution has good compatibility with cement concrete. The obtained cement-based composite material not only has good self-sensing function at room temperature, but also has excellent accuracy and stability in severe cold and freezing environments.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention provides a temperature sensing composite solution for cement, wherein the raw materials include, by weight:

[0008]

[0009] Furthermore, the carbon nanotubes are industrial-grade multi-walled carbon nanotubes with a diameter of 10 to 30 nm, a length of 10 to 30 μm, and a purity of ≥95%.

[0010] The ethylene-vinyl acetate copolymer emulsion is of high solid content type, with a non-volatile matter content of ≥60wt% and a vinyl acetate content of 18-24wt%.

[0011] The solid content of the superplasticizer is 35%, and the water reduction rate is 45%.

[0012] The present invention also provides a method for preparing the temperature sensing composite solution for cement, comprising the following steps:

[0013] (1) adding carbon nanotubes and a superplasticizer into water and dispersing them to obtain a carbon nanotube dispersion;

[0014] (2) The carbon nanotube dispersion and ethylene-vinyl acetate copolymer emulsion are mixed by high-speed shearing to obtain a composite solution.

[0015] Furthermore, in the step (1), the carbon nanotubes are first added to water and ultrasonically dispersed for 10 to 15 minutes at an ultrasonic power of 200 W; then a superplasticizer is added to the above solution and ultrasonically dispersed for another 10 to 15 minutes at an ultrasonic power of 200 W to obtain a carbon nanotube dispersion.

[0016] In the step (2), the ethylene-vinyl acetate copolymer emulsion is added to the carbon nanotube dispersion, and mixed by a high-speed shearing instrument at 6000-8000 rpm for 8-12 minutes to obtain the composite solution.

[0017] The present invention also provides a cement-based temperature sensor, comprising a matrix and an electrode located in the matrix, wherein the matrix is ​​obtained by mixing and solidifying the above-mentioned cement temperature sensing composite solution and composite silicate cement, or by mixing and solidifying the cement temperature sensing composite solution prepared by the above-mentioned preparation method and composite silicate cement.

[0018] Furthermore, according to the mass ratio, the composite solution: composite silicate cement = 30-40:100.

[0019] Furthermore, the working temperature of the cement-based temperature sensor is -30 to 60°C.

[0020] The electrodes used in the temperature sensor can be common electrodes such as copper electrodes.

[0021] The technical solution of the present invention has the following advantages:

[0022] (1) When preparing the composite solution of the present invention, the carbon nanotubes are first placed in water for ultrasonic dispersion, so that the interior of the tube wall is fully saturated with water. Then, the ionic superplasticizer is added thereto and ultrasonicated together with the carbon nanotubes, which can not only weaken the van der Waals force between nanotube molecules through ionic repulsion and improve the dispersion uniformity of the carbon nanotubes, but also prevent the superplasticizer from being adsorbed into the interior of the carbon nanotubes, thereby reducing the water-reducing effect of cement particles.

[0023] (2) An appropriate amount of high-solid content ethylene-vinyl acetate copolymer emulsion is added to the composite solution of the present invention, and the dispersion stability of carbon nanotubes is improved by controlling the vinyl acetate content to 18-24%, and limiting the amount of polymer emulsion added to provide a moderate viscosity. The prepared solution can achieve the phenomenon of no carbon nanotube precipitation for more than 14 days, and the slurry formed after mixing with cement has good fluidity, which is convenient for the subsequent mass production of cement-based temperature sensors.

[0024] (3) The composite solution containing carbon nanotubes, ethylene-vinyl acetate copolymer emulsion and superplasticizer synthesized by the present invention is added to cement-based materials to form a carbon nanotube conductive network structure coated with a polymer film during the cement hydration process. When the sensor prepared by the present invention is used under natural conditions, the ethylene-vinyl acetate film coated on the surface of the carbon nanotubes has good waterproof and water-blocking functions, which can prevent moisture from entering the conductive channel and affecting the perception accuracy of the carbon nanotube conductive network. The resistivity-temperature relationship of the cement-based temperature sensor produced by the process of the present invention shows an obvious linear law (that is, the internal temperature of the concrete can be intuitively and accurately evaluated and monitored through the resistivity change). Especially under negative temperature conditions, the sensor has a high temperature recognition accuracy and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is the elevation view of cement-based temperature sensor;

[0026] Figure 2 is a cross-sectional view of a cement-based temperature sensor;

[0027] Figure 3 The resistivity-temperature curve measured for the sensor prepared in Example 3;

[0028] Figure 4 The resistivity-temperature curve measured for the sensor prepared in Example 4;

[0029] Figure 5 The resistivity-temperature curve measured by the sensor prepared in Comparative Example 3;

[0030] Figure 6 This is the resistivity-temperature curve of the sensor prepared in Comparative Example 4. DETAILED DESCRIPTION

[0031] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0032] In the present application, the carbon nanotubes used in the examples are industrial-grade multi-walled carbon nanotubes with a diameter of 10 to 30 nm, a length of 10 to 30 μm, and a purity of ≥95%;

[0033] The superplasticizer is produced by Kezhijie New Materials Group Co., Ltd., ionic type, solid content 45%, water reduction rate 35%;

[0034] The ethylene-vinyl acetate copolymer emulsion is of high solid content type, with a non-volatile matter content of ≥60wt% and a vinyl acetate content of 18-24wt%.

[0035] The composite silicate cement is PC 42.5 cement produced by Guangdong Tapai Group Co., Ltd.

[0036] If no specific experimental steps or conditions are specified in the examples, the experiments can be carried out according to the conventional experimental steps or conditions described in the literature in the art.

[0037] The following specific examples are further explanations of the present invention. The examples cited cannot list all the embodiments of the present invention. Only some of the embodiments are used as examples for explanation. The specific examples are as follows:

[0038] 1. Preparation of composite solution

[0039] Example 1

[0040] This embodiment provides a temperature sensing composite solution for cement, the raw materials of which include 0.3 kg of carbon nanotubes; 2 kg of superplasticizer; 8 kg of high solid content ethylene-vinyl acetate copolymer emulsion; and 21.8 kg of water. The specific preparation method is as follows:

[0041] (1) First, 0.3 kg of carbon nanotubes were dispersed in 21.8 kg of water by ultrasonication for 15 minutes at an ultrasonic power of 200 W; then 2 kg of superplasticizer was added, and ultrasonication was performed again for 15 minutes at an ultrasonic power of 200 W to obtain a carbon nanotube dispersion;

[0042] (2) 8 kg of high solid content ethylene-vinyl acetate copolymer emulsion was poured into the carbon nanotube dispersion and mixed by a high-speed shearing device at 7000 rpm for 10 minutes to obtain a composite solution.

[0043] Example 2

[0044] This embodiment provides a temperature sensing composite solution for cement, the raw materials of which include 0.3 kg of carbon nanotubes; 2 kg of superplasticizer; 13 kg of high solid content ethylene-vinyl acetate copolymer emulsion; and 19.8 kg of water. The specific preparation method is as follows:

[0045] (1) First, 0.3 kg of carbon nanotubes were dispersed in 19.8 kg of water by ultrasonication for 15 minutes at an ultrasonic power of 200 W; then 2 kg of superplasticizer was added, and ultrasonication was performed again for 15 minutes at an ultrasonic power of 200 W to obtain a carbon nanotube dispersion;

[0046] (2) 14 kg of high solid content ethylene-vinyl acetate copolymer emulsion was poured into the carbon nanotube dispersion and mixed by a high-speed shearing device at 7000 rpm for 10 minutes to obtain a composite solution.

[0047] Comparative Example 1

[0048] A temperature sensing composite solution for cement, the raw materials of which include 0.3kg carbon nanotubes, 2kg superplasticizer, and 25kg water. The specific preparation method is as follows:

[0049] (1) First, 0.3 kg of carbon nanotubes were dispersed in 25 kg of water by ultrasonic dispersion for 15 minutes at an ultrasonic power of 200 W; then 2 kg of superplasticizer was added, and ultrasonic dispersion was performed again for 15 minutes at an ultrasonic power of 200 W to obtain a composite solution.

[0050] Comparative Example 2

[0051] This embodiment provides a cement-based temperature sensor composite solution, the raw materials of which include 0.3 kg of carbon nanotubes; 2 kg of superplasticizer; 20 kg of high solid content ethylene-vinyl acetate copolymer emulsion; and 17.8 kg of water. The specific preparation method is as follows:

[0052] (1) First, 0.3 kg of carbon nanotubes were dispersed in 17.8 kg of water by ultrasonication for 15 minutes at an ultrasonic power of 200 W; then 2 kg of superplasticizer was added, and ultrasonication was performed again for 15 minutes at an ultrasonic power of 200 W to obtain a carbon nanotube dispersion;

[0053] (2) Pour 20 kg of high solid content ethylene-vinyl acetate copolymer emulsion into the carbon nanotube dispersion and mix with a high-speed shearing device at 7000 rpm for 10 minutes to obtain a composite solution.

[0054] The composite solutions prepared in Example 1-2 and Comparative Example 1-2 were stored in the same environment to observe their stability. The results are shown in Table 1. It can be seen that by controlling the vinyl acetate content in the emulsion to 18-24% and adding a suitable amount of emulsion, the dispersion stability of carbon nanotubes can be improved, and the configured solution can achieve no carbon nanotube precipitation for up to 14 days, which is convenient for the subsequent mass production of the composite solution.

[0055] Table 1 Performance comparison of different composite solutions

[0056]

[0057] 2. Preparation of cement-based temperature sensor

[0058] Example 3

[0059] This embodiment provides a cement-based temperature sensor, which is prepared using the composite solution of embodiment 1. The specific preparation method is as follows:

[0060] (1) The composite solution prepared in Example 1 and 100 kg of composite silicate cement were placed in a cement slurry mixer and stirred for 3 minutes to obtain a cement-based temperature sensing composite slurry;

[0061] (2) The obtained composite slurry is placed in a cubic mold, and two copper electrodes are vertically inserted into the slurry at equal intervals. After natural curing for 1 day, the mold is removed and the curing is continued for 28 days to obtain a cement-based temperature sensor.

[0062] Example 4

[0063] This embodiment provides a cement-based temperature sensor, which is prepared using the composite solution of embodiment 2. The specific preparation method is as follows:

[0064] (1) The composite solution prepared in Example 2 and 100 kg of composite silicate cement were placed in a cement slurry mixer and stirred for 3 minutes to obtain a cement-based temperature sensing composite slurry;

[0065] (2) The obtained composite slurry is placed in a cubic mold, and two copper electrodes are vertically inserted into the slurry at equal intervals. After natural curing for 1 day, the mold is removed and the curing is continued for 28 days to obtain a cement-based temperature sensor.

[0066] Comparative Example 3

[0067] A cement-based temperature sensor is prepared using the composite solution of Comparative Example 1. The specific preparation method is as follows:

[0068] (1) The composite solution prepared in Comparative Example 1 and 100 kg of composite silicate cement were placed in a cement slurry mixer and stirred for 3 minutes to obtain a cement-based temperature sensing composite slurry;

[0069] (2) The obtained composite slurry is placed in a cubic mold, and two copper electrodes are vertically inserted into the slurry at equal intervals. After natural curing for 1 day, the mold is removed and the curing is continued for 28 days to obtain a cement-based temperature sensor.

[0070] Comparative Example 4

[0071] A cement-based temperature sensor is prepared using the composite solution of Comparative Example 2. The specific preparation method is as follows:

[0072] (1) The composite solution prepared in Comparative Example 2 and 100 kg of composite silicate cement were placed in a cement slurry mixer and stirred for 3 minutes to obtain a cement-based temperature sensing composite slurry;

[0073] (2) The obtained composite slurry is placed in a cubic mold, and two copper electrodes are vertically inserted into the slurry at equal intervals. After natural curing for 1 day, the mold is removed and the curing is continued for 28 days to obtain a cement-based temperature sensor.

[0074] The structures of the cement-based sensors obtained in Examples 3-4 and Comparative Examples 3 and 4 are as follows: Figure 1-2 The mold size is 50mm×50mm×50mm, the electrode is a copper mesh, and the two-electrode method is used. The copper mesh size is 40mm×60mm, the thickness is 1mm, and the distance between the two electrodes is 20mm.

[0075] The cement-based temperature sensing composite slurry obtained in Examples 3 and 4 and Comparative Examples 3 and 4 was tested for its fluidity; the obtained temperature sensor was tested for its resistivity-temperature corresponding curve. The results are shown in Table 2. For specific curves, please refer to Figure 3-6 .

[0076] Table 2 Performance comparison of temperature sensor examples and comparative examples

[0077]

[0078] By comparison, it can be seen that the slurry obtained by mixing the composite solution obtained by adding an appropriate amount of ethylene-vinyl acetate copolymer emulsion with cement has moderate fluidity, which is convenient for subsequent application in the molding of cement-based temperature sensors and can be mass-produced.

[0079] The temperature sensor obtained in Example 3-4 ( Figure 3-4), not only has good sensing linearity and repeatability in a positive temperature environment (5-60°C) (the resistance value decreases / increases monotonically with temperature rise / fall, and shows good recoverability), but also has good resistivity-temperature corresponding linear relationship and stability in a negative temperature environment (-30-0°C) (the resistance value-temperature still maintains a monotonous linear corresponding relationship, and the resistivity drift is small during the temperature recovery process). The sensor in comparative example 3 ( Figure 5 ) Although it has certain temperature monitoring function and repeatability in positive temperature environment (5-60℃), its linearity is not high. In addition, there is a large error in the resistance change during the heating and cooling process in the negative temperature environment (-30-0℃) (the resistance value deviation is large due to factors such as frost heave deformation during the temperature recovery process), and it is impossible to accurately monitor the temperature in severe cold and frozen environments. The sensor in Example 4 ( Figure 6 ), because the excessive addition of ethylene-vinyl acetate copolymer emulsion provides strong viscosity, the slurry produced during the mixing of the composite solution and cement has very poor fluidity, and the uniform distribution of the components cannot be achieved, resulting in a decrease in the linearity and repeatability of the resistivity-temperature correspondence. This shows that only by introducing a suitable amount of high-solid content ethylene-vinyl acetate copolymer emulsion into the carbon nanotube-cement-based sensor through the process of the present invention can the linearity of the temperature sensor and the monitoring reliability and stability in a low-temperature environment be significantly improved.

[0080] From the above, it can be seen that the composite solution containing carbon nanotubes, ethylene-vinyl acetate copolymer emulsion and superplasticizer synthesized in the embodiment of the present invention has good stability and is conducive to industrial large-scale production and storage.

[0081] The composite solution of the present invention is added to cement-based materials to form a carbon nanotube conductive network structure coated with a polymer film during cement hydration, which can significantly improve the linearity of the temperature sensor and the monitoring reliability and stability in a low temperature environment. Moreover, the polymer film and the carbon nanotubes together improve the toughness and plasticity of the cement substrate, and the obtained temperature sensor can also have a good sensing effect at low temperatures. Moreover, the ethylene-vinyl acetate film coated on the surface of the carbon nanotubes has good waterproof and water-blocking functions, which can prevent moisture from entering the conductive channel and affecting the sensing accuracy of the carbon nanotube conductive network. Compared with traditional sensors, the cement-based temperature sensor of the embodiment of the present invention has an obvious linear law in the resistivity-temperature relationship (that is, the internal temperature of the concrete can be intuitively and accurately evaluated and monitored through resistivity changes). Especially at negative temperatures, around minus 30°C, it still has a high temperature recognition accuracy and stability.

[0082] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A composite solution for realizing the temperature sensing function of cement-based materials, characterized in that: In parts by mass, including:

2. The composite solution according to claim 1, characterized in that: The carbon nanotubes are industrial-grade multi-walled carbon nanotubes with a diameter of 10 to 30 nm, a length of 10 to 30 μm, and a purity of ≥95%.

3. The composite solution according to claim 1, characterized in that: The ethylene-vinyl acetate copolymer emulsion is of high solid content type, with a non-volatile matter content of ≥60wt% and a vinyl acetate content of 18-24wt%.

4. The composite solution according to claim 1, characterized in that: The solid content of the superplasticizer is 35%, and the water reduction rate is 45%.

5. The method for preparing the composite solution according to any one of claims 1 to 4, characterized in that: The steps include: (1) adding carbon nanotubes and a superplasticizer into water and dispersing them to obtain a carbon nanotube dispersion; (2) The carbon nanotube dispersion and ethylene-vinyl acetate copolymer emulsion are mixed by high-speed shearing to obtain a composite solution.

6. The preparation method according to claim 5, characterized in that: In the step (1), the carbon nanotubes are first added to water and ultrasonically dispersed for 10 to 15 minutes at an ultrasonic power of 200 W; then a superplasticizer is added to the solution and ultrasonically dispersed for 10 to 15 minutes at an ultrasonic power of 200 W to obtain a carbon nanotube dispersion.

7. The preparation method according to claim 5, characterized in that: In the step (2), the ethylene-vinyl acetate copolymer emulsion is added to the carbon nanotube dispersion, and mixed by a high-speed shearing instrument at 6000-8000 rpm for 8-12 minutes to obtain the composite solution.

8. A cement-based temperature sensor, comprising a matrix and an electrode located in the matrix, wherein the matrix is ​​obtained by mixing and solidifying the temperature sensing composite solution for cement according to any one of claims 1 to 4 and composite silicate cement, or by mixing and solidifying the temperature sensing composite solution for cement prepared by the preparation method according to any one of claims 5 to 7 and composite silicate cement.

9. The cement-based temperature sensor according to claim 8, characterized in that: According to the mass ratio, composite solution: composite silicate cement = 30-40:

100.

10. The cement-based temperature sensor according to claim 8, characterized in that: The working temperature of the cement-based temperature sensor is -30 to 60°C.

Citation Information

Patent Citations

  • Manufacturing method for temperature sensor

    CN103674300A